THE ROLE OF BAPAS IN THE IMPLEMENTATION OF THE CHILD CRIMINAL SYSTEM - Rama Fatahillah Yulianto; Ali Muhammad (Polteknik Ilmu Pemasyarakatan, 2021)
The role of the Fathers, LPKA and LPAS in the Juvenile Criminal Justice System since the enactment of the Juvenile Criminal Justice System Act is getting bigger and more important this is because the Correctional Center (BAPAS) through the Community Counselor (PK) has had to work since the pre-adjudication stage, this is shown through the implementation of assistance by the Community Advisor (PK) since the child is reported to have committed a crime and this is regulated in the Child Criminal Justice System Act, then the Community Advisor based on the mandate of this Law is also to immediately conduct Community Research (Litmas) within a period of 1 x 24 hours as a basis for investigators to decide whether a child will be resolved through a litigation process or a non-litigation process and the role of the Fathers continues to be carried out at the adjudication stage to post-adjudication. This role reflects that currently Correctional Services through the Correctional Technical Implementing Unit as stipulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System have been carried out since the beginning of the criminal justice system process and are no longer relevant if correctional is in the criminal justice system. This child is positioned to be the final part of the juvenile criminal justice system. This study uses a research method with a statutory approach (statue approach), a conceptual approach (conceptual approach) by examining each norm that regulates the role of the Fathers in each article in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and linking these norms with the concept of and the level of implementation of the Juvenile Criminal Justice System Act (Alam & Purwati, 2016).